Preeklampsia, Diabetes Melitus Gestasional, Infeksi Saluran Kemih, Obesitas, Dan Riwayat Sectio Caesarea Pada Wanita G4P2A1 Usia Kehamilan 36-37 Minggu - Shabira Rabbani P.; Ardian Suryo Anggoro; Damarizqa Dara Sjahruddin (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Preeclampsia in pregnancy complicated by gestational diabetes mellitus and obesity represents a high-risk condition characterized by endothelial dysfunction, severe hypertension, and increased maternal–fetal morbidity. We report a 34-year-old woman, G4P2A1, at 36–37 weeks of gestation who presented with severe hypertension (194/115 mmHg), proteinuria 1+, uncontrolled hyperglycemia (random glucose 230 mg/dL), and a history of two previous cesarean sections. Ultrasonography revealed an appropriately grown fetus with an estimated fetal weight of 3203 grams, and cardiotocography was reactive. The patient’s obesity (BMI 28.8 kg/m²) and poorly controlled gestational diabetes contributed to worsening endothelial injury and progression of preeclampsia. Maternal stabilization was achieved with antihypertensives, magnesium sulfate, insulin sliding scale, and antibiotics for a concurrent urinary tract infection. A repeat cesarean section followed by bilateral salpingectomy was performed with favorable maternal and neonatal outcomes. This case highlights the importance of early detection, intensive antenatal monitoring, and multidisciplinary management in high-risk pregnancies to reduce maternal and perinatal morbidity and mortality.